High temperature oxidation resistance of physical vapor deposited Hf-Si-B-2 +/- z thin films - Glechner, T.; Bahr, A.; Hahn, R.; Wojcik, T.; Heller, Martina; Kirnbauer, A.; Ramm, J.; Kolozsvari, S.; Felfer, Peter; Riedl, H. (Corrosion Science, 2022)
Within physical vapor deposited Hf-Si-B-2 +/- z thin films, selective diffusion-driven oxidation of Si is identified to cause outstanding oxidation resistance at temperatures up to 1500 degrees C. After 60 h at 1200 degrees C, the initially 2.47 mu m thin Hf0.20Si0.23B0.57 thin film exhibits a dense oxide scale of only 1.56 mu m. The thermally induced decomposition of metastable Hf-Si-B-2 +/- z leads not only to the formation of Si precipitates within the remaining thin film (related to a non-homogenous Si distribution after the deposition) but also to pure Si layers on top and bottom of the Hf-Si-B-2 +/- z coatings next to the excellent adherend SiO2 based scales.
CRIS-Team WoS Importer:2022-07-15